Weathering and erosion of fractured bedrock systems. Issue 13 (20th July 2017) - Lebedeva, Marina I.; Brantley, Susan L.
Abstract: We explore the contribution of fractures (joints) in controlling the rate of weathering advance for a low‐porosity rock by using methods of homogenization to create averaged weathering equations. The rate of advance of the weathering front can be expressed as the same rate observed in non‐fractured media (or in an individual block) divided by the volume fraction of non‐fractured blocks in the fractured parent material. In the model, the parent has fractures that are filled with a more porous material that contains only inert or completely weathered material. The low‐porosity rock weathers by reaction‐transport processes. As observed in field systems, the model shows that the weathering advance rate is greater for the fractured as compared to the analogous non‐fractured system because the volume fraction of blocks is < 1. The increase in advance rate is attributed both to the increase in weathered material that accompanies higher fracture density, and to the increase in exposure of surface of low‐porosity rock to reaction‐transport. For constant fracture aperture, the weathering advance rate increases when the fracture spacing decreases. Equations describing weathering advance rate are summarized in the 'List of selected equations'. If erosion is imposed at a constant rate, the weathering systems with fracture‐bounded bedrock blocks attain a steady state. In the erosional transport‐limited regime, bedrock blocks no longer emerge at the air‐regolith boundary because they weather away. In the weathering‐limited (or kinetic) regime, blocks of various size become exhumed at the surface and the average size of these exposed blocks increases with the erosion rate. For convex hillslopes, the block size exposed at the surface increases downslope. This model can explain observations of exhumed rocks weathering in the Luquillo mountains of Puerto Rico. Published 2017. This article is a U.S. Government work and is in the public domain in the USA